Immunogenicity and reactogenicity of COVID-19 Pfizer-BioNTech (Bnt162b2) mRNA vaccination in immunocompromised adolescents and young adults: a systematic review and meta-analyses. (31st December 2023) - Katoto, Patrick DMC; Kakubu, Mireille AM; Tamuzi, Jacques L.; Brand, Amanda S.; Ayuk, Adaeze; Byamungu, Liliane N.; Wiysonge, Charles S.; Gray, Glenda
ABSTRACT: Background: This study aimed to evaluate the safety and effectiveness of the BNT162b2 vaccine in immunocompromised adolescents and young adults. Research design and methods: The study conducted a meta-analysis of post-marketing studies examining BNT162b2 vaccination efficacy and safety among immunocompromised adolescents and young adults worldwide. The review included nine studies and 513 individuals aged between 12 and 24.3 years. The study used a random effect model to estimate pooled proportions, log relative risk, and mean difference, and assessed heterogeneity using the I2 test. The study also examined publication bias using Egger's regression and Begg's rank correlation and assessed bias risk using ROBINS-I. Results: The pooled proportions of combined local and systemic reactions after the first and second doses were 30% and 32%, respectively. Adverse events following immunization (AEFI) were most frequent in rheumatic diseases (40%) and least frequent in cystic fibrosis (27%), although hospitalizations for AEFIs were rare. The pooled estimations did not show a statistically significant difference between immunocompromised individuals and healthy controls for neutralizing antibodies, measured IgG, or vaccine effectiveness after the primary dose. However, the evidence quality is low to moderate due to a high risk of bias, and no study could rule out the risk of selection bias, ascertainment bias, or selective outcome reporting. Conclusions: This study provides preliminary evidence that the BNT162b2 vaccine is safe and effective in immunocompromised adolescents and young adults, but with low to moderate evidence quality due to bias risk. The study calls for improved methodological quality in studies involving specific populations.